A recommended paradigm for vaccination of rheumatic disease patients with the SARS-CoV-2 vaccine. Issue 121 (July 2021) - Moutsopoulos, Haralampos M.
Abstract: Autoimmune and autoinflammatory rheumatic disorders (ARD) are treated with antimetabolites, calcineurin inhibitors and biologic agents either neutralizing cytokines [Tumor Necrosis Factor (TNF), Interleukin (IL)-1, IL-6, IL-17, B-cell activating factor] or being directed against B-cells (anti-CD-20), costimulatory molecules or JAK kinases. Similarly for the influenza or pneumococcal vaccines, there is limited data on the effectiveness of vaccination against SARS-CoV-2 infection and COVID-19 prevention for this susceptible patient population. Moreover, preliminary data from vaccinated organ transplanted, inflammatory bowel and connective tissue disease patients suggests only limited immunogenicity after the first vaccine dose, particularly in patients on immunosuppressive regimens. Herein a set of recommendations for the vaccination of immune suppressed patients with the SARS-CoV-2 vaccines is proposed aimed at achieving optimal vaccine benefit without interfering with disease activity status. Moreover, rare autoimmune adverse events related to vaccinations are discussed. Highlights: Data on effectiveness of SARS-CoV-2 vaccination in patients with rheumatic diseases is limited. Disease remission at the time of vaccination is desirable. Modifications in immunosuppressive/immunomodulatory treatment regimens is recommended. Testing for antibodies against SARS-CoV-2 proteins is proposed following vaccination.